2008
DOI: 10.1017/s0022381607080127
|View full text |Cite
|
Sign up to set email alerts
|

Older but Wiser? Effects of Age on Political Cognition

Abstract: In experimental studies of voter's information processing, Lau and Redlawsk (2006) found one control variable to have pervasive effects in their analyses: age. Age was associated with less information search, less memory, less accurate memory, and a lower probability of making a correct vote. Reexamining those experimental studies, we find that inexperience with computers and slower manual dexterity are both associated with less information access, but controlling on these factors, age continues to have a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…We expect a positive relationship between age and political knowledge, although a decline in this relationship has been demonstrated in advanced ages in previous works (Lau and Redlawsk, 2009). For this reason, Age (in years) and Age (squared) (to capture a potential non-linear relationship) are included in the models.…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…We expect a positive relationship between age and political knowledge, although a decline in this relationship has been demonstrated in advanced ages in previous works (Lau and Redlawsk, 2009). For this reason, Age (in years) and Age (squared) (to capture a potential non-linear relationship) are included in the models.…”
Section: Methodsmentioning
confidence: 65%
“…According to the previous literature, the variable should enter positively in the model as men tend to show higher levels of political knowledge than women (see Fraile, 2014). • We expect a positive relationship between age and political knowledge, although a decline in this relationship has been demonstrated in advanced ages in previous works (Lau and Redlawsk, 2009). For this reason, Age (in years) and Age (squared) (to capture a potential non-linear relationship) are included in the models.…”
Section: Methodsmentioning
confidence: 97%
“…This downplays situations in which one particular pro argument trumps all other contra arguments. While this is certainly possible, several studies of decision making have shown that it does not really make a difference whether or not weighting of different arguments is applied to determine voters’ preferences on a particular initiative (Lau and Redlawsk ; Milic ). Moreover, some arguments (in particular those that were declared pro or contra beforehand, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our welfare states and the dominant role of pensions can be explained by 'gerontocracy', that is, the elderly represent an interest-group which is successful in exerting political power and obtaining transfers in its favor (Mulligan and Sala-i-Martin 2003). Age also influences the ability of voters to process information and to make a correct vote, as discussed in Lau and Redlawsk (2008).…”
Section: Introductionmentioning
confidence: 99%